Validation of measurement scale for technostress in Peruvian university students - Verde-Avalos, Emilyn; Turpo-Chaparro, Josué Edison; Palomino-Ccasa, Joel; Requena-Cabral, Gabriela; Malca-Peralta, Segundo Salatiel (Frontiers in Psychology, 2025)
Stress has become one of the major health issues worldwide, and the mandatory integration of technologies into the educational environment has exacerbated this problem. This situation affects both teachers and students, who often lack the necessary knowledge to use these tools effectively, putting their mental health and emotional well-being at risk across various areas. Over the years, numerous studies have been conducted on technostress in both workplace and educational contexts, analyzing its causes and consequences, as well as psychometric evaluations of instruments related to technological adaptation. This study presents an instrumental design and cross-sectional approach, with 814 Peruvian university students voluntarily participating, consisting of both sexes (451 females; 55%) aged between 18 and 36 years (M = 25.2, SD = 5.12). The instrument used was the Technostress Questionnaire for University Students (TS4US), initially developed for Chinese university students, which underwent a cultural adaptation process, expert judgment, and pilot testing. The exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) of the TS4US versions revealed that the 11-item version maintained the three original dimensions, showing an excellent fit with indices of CFI = 0.982, TLI = 0.975, RMSEA = 0.007, and SRMR = 0.02, along with high internal consistency, with Alpha and Omega coefficients greater than 0.86. These results confirm that the TS4US is a valid and reliable tool for measuring technostress in Peruvian university students.